Early variations in lymphocytes and T lymphocyte subsets are associated with radiation pneumonitis in lung cancer patients and experimental mice received thoracic irradiation. (24th March 2020) - Zhou, Pu; Chen, Lu; Yan, Dong; Huang, Changlin; Chen, Guangpeng; Wang, Zhiyi; Zhong, Liangzhi; Luo, Wen; Chen, Diangang; Chun, Chui; Zhang, Shushu; Li, Guanghui
Abstract: There were no ideal markers to predict the development of radiation pneumonitis (RP). We want to investigate the value of variations of lymphocytes and T lymphocyte subsets in predicting RP after radiotherapy (RT) of lung cancer based on previous clinical findings. A total of 182 lung cancer patients who received RT were retrospectively analyzed. Circulating lymphocytes and T lymphocyte subsets were measured before, during, and after RT. Patients were evaluated from the start of RT to 6 months post‐RT. A mice model with acute radiation‐induced lung injury was established and circulating lymphocytes were measured weekly until 8 weeks after irradiation. Univariate and multivariate analyses were adopted to identify risk factors of RP. Lymphocyte levels significantly decreased ( P  < .001) in patients before RP symptoms developed that also was able to be seen in the mice model and the values recovered during remission of symptoms. The decrease in lymphocyte count reflected the severity of RP. Meanwhile, CD4 +  T lymphocyte count was significantly lower during the occurrence of symptoms in patients with RP than in those without RP ( P  < .001), and it improved along with RP recovery. Levels of lymphocytes and CD4 +  T lymphocyte subsets proved as independent predictors of RP. Here we showed that lower peripheral blood levels of lymphocytes and CD4 +  T lymphocyte were associated with an increased risk of RP, which was validated by this mice model, and thus are associated with differences in radiation‐induced lung toxicity among individuals and help identify those who are susceptible to developing RP after RT. Abstract : We found lower levels of lymphocyte and CD4 +  T lymphocyte linked with radiation pneumonitis and dynamic change of lymphocyte and CD4 +  T lymphocyte predict radiation pneumonitis after 182 cases of lung cancer patients with radiation pneumonitis were retrospectively analyzed. The relation of lymphocytes change and radiation pneumonitis was also confirmed in mice model. Therefore, decrease in lymphocyte and CD4 +  T lymphocyte was able to act as a predictor of radiation pneumonitis in patients who received thoracic radiotherapy.